If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5y + -4x)(5y + 4x) = 0 Reorder the terms: (-4x + 5y)(5y + 4x) = 0 Reorder the terms: (-4x + 5y)(4x + 5y) = 0 Multiply (-4x + 5y) * (4x + 5y) (-4x * (4x + 5y) + 5y * (4x + 5y)) = 0 ((4x * -4x + 5y * -4x) + 5y * (4x + 5y)) = 0 Reorder the terms: ((-20xy + -16x2) + 5y * (4x + 5y)) = 0 ((-20xy + -16x2) + 5y * (4x + 5y)) = 0 (-20xy + -16x2 + (4x * 5y + 5y * 5y)) = 0 (-20xy + -16x2 + (20xy + 25y2)) = 0 Reorder the terms: (-20xy + 20xy + -16x2 + 25y2) = 0 Combine like terms: -20xy + 20xy = 0 (0 + -16x2 + 25y2) = 0 (-16x2 + 25y2) = 0 Solving -16x2 + 25y2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25y2' to each side of the equation. -16x2 + 25y2 + -25y2 = 0 + -25y2 Combine like terms: 25y2 + -25y2 = 0 -16x2 + 0 = 0 + -25y2 -16x2 = 0 + -25y2 Remove the zero: -16x2 = -25y2 Divide each side by '-16'. x2 = 1.5625y2 Simplifying x2 = 1.5625y2 Take the square root of each side: x = {-1.25y, 1.25y}
| 4x^2y(2xy-3xy^2+5x^2)= | | cos(12x)= | | M-4n=-8 | | x^(3/2)=9x^(3/4)-20 | | 5x^(6/5)=14x^(3/5)-8 | | x/.25=625 | | -5x+3=16x^2+56+49 | | -7x-10=64(-2x-2) | | qd=500-10p | | 8a^2+10a-13=0 | | B/4=3/2 | | 6x^(1/2)=14x^(1/4)-8 | | 4-3x=4-9x | | x=3x^(1/2)-2 | | 6+6=8I | | C(x)=30.50-0.25x | | 42x=32 | | 4x^2-8x+4=36(-5x-3) | | 5x-3=9x^2-24+16 | | 5x^8/5=11x^4/5-2 | | 4w+60+2w=460 | | R(3+2)-6(t-5)-22=6 | | 8x-28=0 | | x^2-24x+144-64x-64=0 | | 7b=2-b/7b=3-b | | 4(y+10)=2y+6 | | n-2.5=4n+(-1) | | x^2-5x-6-100=0 | | 2x^2+5x+97-100=0 | | [8(q+5)-16]-[2(q-3)+3]= | | 2(17a+8)= | | 16*22/7 |